Penerapan Good Corporate Governance Terhadap Informasi Kinerja Keuangan di Bank BTN Cilegon - Rohaelis Nuraisiah; Anggi Haerani; Lona Noviani (Progress: Jurnal Pendidikan, Akuntansi dan Keuangan, 2023)
The good corporate governance is the important alternative in a company, especially BUMN. Good corporate governance which has the purpose to become the better healthier company with has the four principles, there are transparency, accountability, fairness and responsibility. These purpose of researches to know how much the influence from the applied toward the finance performance information at PT. Bank Tabungan Negara (Persero) branch Cilegon. The writer use the descriptive method as the research method. The data of paper arranged with to do library study, interview, observation, and questionnaire and to analyze of data used the SPSS 17.0 program for windows. The survey take the sample from employee population of PT. Bank Tabungan Negara (Persero) branch Cilegon which has the sum (n=87). The applied of good corporate governance has the positive influence toward the finance performance information in the company of PT. Bank Tabungan Negara (Persero) branch Cilegon. Based on the result of hypothesis evaluate with method the influence from the applied of good corporate governance (X) toward the finance performance information (Y) in evaluate of t, to get from result of tsum as big as 7,059 while ttable 1,66298 with using the real standard as big as 0,05. Because the tsum 7,059 > ttable 1,66298 and then H0 = rejected and H1 received and then with method the applied good corporate governance have the positive influence toward finance performance information.